Dyslipidemia and Diabetes: Reciprocal Impact of Impaired Lipid Metabolism and Beta-Cell Dysfunction on Micro- and Macrovascular Complications (The Review of Diabetic Studies, 2023)
Patients with diabetes frequently exhibit the combined occurrence of hyperglycemia and dyslipidemia. Published data on their coexistence are often controversial. Some studies provide evidence for suboptimal lifestyle and exogenous hyperinsulinism at “mild insulin resistance” in adult diabetic patients as main pathogenic factors. In contrast, other studies confirm that visceral adiposity and insulin resistance are the basic features of dyslipidemia in type 2 diabetes (T2D). The consequence is an excess of free fatty acids, which causes hepatic gluconeogenesis to increase, metabolism in muscles to shift from glucose to lipid, beta-cell lipotoxicity, and an appearance of the classical “lipid triad”, without real hypercholesterolemia. Recently, it has been proposed that cholesterol homeostasis is important for an adequate insulin secretory performance of beta-cells. The accumulation of cholesterol in beta-cells, caused by defective high-density lipoprotein (HDL) cholesterol with reduced cholesterol efflux, induces hyperglycemia, impaired insulin secretion, and beta-cell apoptosis. Data from animal models and humans, including humans with Tangier disease, who are characterized by very low HDL cholesterol levels, are frequently associated with hyperglycemia and T2D. Thus, there is a reciprocal influence of dyslipidemia on beta-cell function and inversely of beta-cell dysfunction on lipid metabolism and micro- and macrovascular complications. It remains to be clarified how these different but mutually influencing adverse effects act in together to define measures for a more effective prevention and treatment of micro- and macrovascular complications in diabetes patients. While the control of circulating low-density lipoprotein (LDL) cholesterol and the level of HDL cholesterol are determinant targets for the reduction of cardiovascular risk, based on recent data, these targets should also be considered for the prevention of betacell dysfunction and the development of type 2 diabetes. In this review, we analyze consolidated data and recent advances on the relationship between lipid metabolism and diabetes mellitus, with particular attention to the reciprocal effects of the two features of the disease and the development of vascular complications.